Study on Composite Anti - Corrosion Technology of Infiltration Passivation and Sealing for Auxiliary Steel Structure of Concrete Bridge - WANG Tao, DU Cun - shan, ZHU He - quan, SHI Zhen - ping, NAN Yang, JIA Heng - qiong (Cailiao Baohu)
In order to provide long - term anti - corrosion technology for auxiliary steel structures of concrete bridges in the railway industry, based on multi - element powder infiltration technology, systematic research on the water - based passivation solution without heavy metals and toning sealing technology (PCA) was conducted. Then, an anti - corrosion technology for auxiliary steel structure of concrete bridge with neutral salt spray resistance of more than 1 200 h was developed. The microstructure and element distribution of the anti - corrosion coating were studied by SEM and EDS. The results showed that the surface infiltrated layer of steel structure treated by multi - element powder infiltration technology was an alloy layer containing Zn, Fe and Al elements, which was closely combined with the substrate. The passivation solution without heavy metals could form a passivation film on the surface of the infiltrated workpiece, which had good repair and passivation ability for the defects of the infiltrated layer on the workpiece surface. The infiltrated samples after passivation treatment had good salt spray resistance. After salt spray test of 1 200 h, no red rust was found on the sample surface. The corrosion resistance and the aging - resistant performance of the sample could be improved by sealing the samples with the water - based one - component baking paint. The resistance of the neutral salt spray for steel beams treated by PCA technology was more than 1 200 h. After more than 2 years of practical use on site, the effect was good.